A Monetarist Model of the Monetary Process: Discussion - Klein, John J. (Journal of Finance, 1970)
John J. Klein, A Monetarist Model of the Monetary Process: Discussion, The Journal of Finance, Vol. 25, No. 2, Papers and Proceedings of the Twenty-Eighth Annual Meeting of the American Finance Association New York, N.Y. December, 28-30, 1969 (May, 1970), pp. 322-325